Dynamic for the agroecological transition (Dytael) in Fatick - Senegal. Relocalization of the millet value chain for the territorialization of agroecology - Fall, Modou Gueye; Ba, Koki; Sebe, Laetitia; Diene, Rokhaya; Ndour, Maimouna; Faye, Daouda; Sall, Moussa; Diakhaté, Pape Bilal; Camara, Astou Diao; Cesaro, Jean-Daniel (2024)
Senegal's socioeconomic framework, initially developed in 2014 under the Emerging Senegal Plan (PSE), did not explicitly include sustainable development or agroecology due to its pre-SDG context. However, thanks to advocacy efforts and the emerging agroecological transition, the PSE has evolved into PSE_vert, now incorporating agroecology into national policies. Despite this shift, local policies still provide limited support for agroecology. To address this gap, local initiatives such as DyTAEL in Fatick are working to territorialize agroecology. Supported by the One CGIAR agroecological initiative, DyTAEL aims to promote the adoption of agroecology in local development policies. In municipalities like Niakhar, agroecology is now included in municipal development plans (PDCs). These municipalities rely on local initiatives like the Jamm Bugum association, which leads DyTAEL, to implement agroecological actions. Jamm Bugum focuses on developing an integrated millet value chain by creating processing units for millet-based products like couscous and Thiakry, popular in Senegal, and producing composite bread that incorporates 30% millet. The association also supports agroecological millet production and provides commercial opportunities. As the leader of the Agroecology Living Landscape (ALL), Jamm Bugum aims to showcase its integrated value chain model to promote agroecology across the Fatick department.